Exploring the Relationship Between Nutrition Status, Reproductive Health Knowledge, and Anemia in Adolescent Girls in Depok, Sleman, Yogyakarta - Cahya Nirmala Dewinta, Mustika; Gustina, Erni (Epidemiology and Society Health Review (ESHR), 2024)
Background: The issue of anaemia continues to be a significant public health concern requiring attention, mainly due to its increasing prevalence. In Sleman District, it has been observed that the prevalence of anaemia among adolescents has significantly risen from 2016 to 2018. This phenomenon underscores the interconnectedness of nutritional status, reproductive health, and anaemia, especially among adolescent girls. Adolescents, particularly girls, require sufficient nutritional intake to navigate the challenges associated with their physiological changes, particularly those related to the reproductive system. Nutritional status plays a crucial role in influencing reproductive system disorders, impacting menstrual irregularities, and closely intertwining with the occurrence of anaemia among adolescent girls. This paper highlights the relationship between nutrition status, reproductive health knowledge, and anaemia in Depok, Sleman, and Yogyakarta adolescent girls. Method: The study employed a cross-sectional method to explore data concerning nutritional status and reproductive health knowledge variables. The study was conducted on 108 female junior high school students aged 10-15 years in 3 schools in the Depok Sleman District. Sampling was done using accidental sampling. Data was collected at the schools by measuring anthropometry (body weight, height, BMI), checking haemoglobin (Hb), and filling out questionnaires on knowledge and dietary patterns. Results: It was found that there was no significant relationship between nutritional status and anaemia status in adolescents (p-value 0.75). Analysis of the relationship between knowledge related to reproductive health and anaemia status also revealed no significant relationship (p-value 0.772). Conclusion: The study concluded that no significant relationship exists between nutrition status, knowledge related to reproductive health, and anaemia status in adolescent girls. Although the results of this study did not show a significant relationship, the urgency for adolescents to maintain nutritional status and increase knowledge about anaemia prevention remains essential in the effort to prevent anaemia. A comprehensive anaemia prevention program must be implemented through collaboration among schools, health authorities, and the community.